Alteração da competência tributária e reforma constitucional: O ICMS na importação de bens e a EC 33/01 - Loureiro Filho, Mario Hermes Trigo de (2006)
This study is aimed at checking the performance limits of the power of constitutional reform in its permanent manner related to the change of the discrimination of tributary competencies which belong to the political people who are part of the Brazilian State. This is due to the fact of the recent reform cycle of the constitution which through a high number of amendments has been systematically changing the discrimination above mentioned by extinguishing taxes, creating new ones, or even just altering their archetypes. Our main hypothesis is based on the premise that the State power for taxation is practiced by means of tax competencies which are set by the Federal Constitution, and also that the discrimination of such competencies may suffer changes since the performance limits of the constituent derived power are respected. The approach for the theme is still based on a systemic view of the positive law and its specific way to answer to the stimulus of other systems with which it interacts. And among them we highlight the political and economic systems since our hypothesis is closely linked to taxation whose subject was exhaustively dealt with by the Federal Constitution. In this context we analyzed the features of tax competency and the consequences derived from them, as well as the limits imposed to the practice of the power of constitutional reform. After concluding that only by an isolated analysis it is possible to know if the reforming power acted within the limits imposed to it by the originator constituent, our next step was to take into consideration in a specific way the constitutional validity of the EC no. 33/01 which altered the Federal Constitution (art. 155, § 2º, IX, a ) so as to allow the States and Brasília, the Brazilian capital, to establish the ICMS tax also when importing goods